Assessment of health system readiness and quality of dementia services in Peru: protocol for a qualitative study with stakeholder interviews and documentation review - Lazo-Porras,M; Tateishi-Serruto,FJ; Butler,C; Cuba-Fuentes,MS; Rossini-Vilchez,D; Perez-Leon,S; Lucar-Flores,M; Miranda,JJ; Bernabe-Ortiz,A; Diez-Canseco,F; Moore,G; Landeiro,F; et al. (JMIR Research Protocols, 2025)
Background:Dementia is a global health priority with significant challenges due to its complex nature and increasing prevalence. Health systems worldwide struggle to address chronic conditions like dementia, often providing fragmented care. However, information about how health systems respond to the needs of people with dementia and their carers, and the quality of care provided, is scarce in low- and middle-income countries.Objective:This study aims to assess the quality of the health system to provide diagnosis and care for people with dementia and their carers in Peru. In order to do this, the study will explore the response of the Peruvian health system to people with dementia and their carers, and explore the experiences of people with dementia of receiving their diagnosis, management, and quality of care for this condition.Methods:This study is part of a research program called “IMPACT Salud: Innovations using Mhealth for people with dementia and Co-morbidities,” aimed at strengthening health systems to provide care for people with dementia and their carers. The study has a descriptive, cross-sectional design that uses a qualitative methodology, including stakeholder interviews and documentation review, and consists of 2 substudies, a health system assessment (HSA) and an exploration of the patient journey. The first substudy uses an HSA methodology suitable for low- and middle-income countries, conducting 160 structured interviews with 12 different stakeholder types across 3 levels of the health system (micro, meso, and macro) in 4 Peruvian regions, each with distinct geographical and urbanization profiles. The second substudy uses a patient journey methodology, which involves conducting 40 in-depth interviews with people with dementia, carers, and health care workers from the same 4 regions. The insights into the people with dementia patient and caregiver experience within the health system from the interviews will be used to produce a patient j